Impacto da educação patrimonial na formação de professores do município de Vigia de Nazaré - SILVA, Luiz Rocha da (Universidade Federal do Pará, 2012)
The focus of this project of Heritage Education is based on dialy elements and local culture in the city of Vigia de Nazaré, in the state of Pará, Brazil. The main objective of this investigation was to intervene in the pedagogical practice of the teachers in Vigia, with the proposal to give to them methodological subsidies to work with Heritage Education. Also verifying, from the point of view of environmental evaluation and recovering the memory of cultural identity, the content and the possibilities that can be pedagogically worked in the classroom using Heritage Education. To reach this objective, among the priorities used were the formation workshops with 31 teachers who provided individual and collective registers, observations, lessons outings, museum goings and making of script. The results showed that the subjects of the workshops could realize the cultural and social implications of Heritage Education in formal and non-formal educational field. Teachers, students and community were influenced by the collective commitment to preserve and to conserve the local social environment and heritage culture. Even with the levels of destruction of the heritage environment and the feeling of losing the cultural identity in the city, the work had its positive results in the sense that the participants became concerned with the formulation of new planning that includes the Heritage Education in school curriculums. The incentive to use Heritage Education had a good repercussion from the teachers understanding, since they demonstrated a viable practice to take to the schools a consistent reflection on how to articulate the role of the school, social justice, public space and the teacher’s collective knowledge. Heritage Education is a way to form an educational consciousness to experiment a transversal approach and use heritage resources as objects of a cultural, historical and scientific investigation.